2015
DOI: 10.3389/fpsyg.2015.01691
|View full text |Cite
|
Sign up to set email alerts
|

Processing of masked and unmasked emotional faces under different attentional conditions: an electrophysiological investigation

Abstract: In order to investigate the interactions between non-spatial selective attention, awareness and emotion processing, we carried out an ERP study using a backward masking paradigm, in which angry, fearful, happy, and neutral facial expressions were presented, while participants attempted to detect the presence of one or the other category of facial expressions in the different experimental blocks. ERP results showed that negative emotions enhanced an early N170 response over temporal-occipital leads in both mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 77 publications
6
37
2
Order By: Relevance
“…: [ 52 53 ]). Our interpretation is also consistent with results suggesting that fearful stimuli recruit more attentional resources (see: [ 54 ]), and their detection occurs earlier than for neutral stimuli [ 46 , 55 ]. This, in turn, again suggests that all of the ERP components analysed within the study are not necessarily NNC, but they instead reflect higher sensitivity of the system to important stimuli that only later could give rise to awareness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…: [ 52 53 ]). Our interpretation is also consistent with results suggesting that fearful stimuli recruit more attentional resources (see: [ 54 ]), and their detection occurs earlier than for neutral stimuli [ 46 , 55 ]. This, in turn, again suggests that all of the ERP components analysed within the study are not necessarily NNC, but they instead reflect higher sensitivity of the system to important stimuli that only later could give rise to awareness.…”
Section: Discussionsupporting
confidence: 92%
“…that negativity is even more enhanced than the negativity which is a result of the face processing components). However, it also may be suggested that the more pronounced N170 and EPN components reflect a more detailed, sensitive and focussed processing of facial stimulus that only at later stages of processing result in higher awareness [ 45 46 ]. Thus, N170 and EPN would be necessary but not sufficient correlates of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on attention has primarily focused on the issues of whether attention modulates early as well as late processes. Our study confirms that attention can have a strong modulating influence on early components, although withdrawal of attention does not completely eradicate them ( Feng et al 2012 ; Hillyard and Anllo-Vento 1998 ; Kastner and Ungerleider 2000 ; Luck and Ford 1998 ; Woodman and Luck 2003 ; Zotto and Pegna 2015 ). However, our study points to another way in which attention impacts perceptual processing.…”
Section: Discussionsupporting
confidence: 77%
“…Researchers have used ERPs to measure the time-course of processing facial expressions. A number of studies indicated that even when awareness of emotional facial expressions was restricted using backward masking, multiple ERP components were modulated by negative target faces (fear and anger) compared to non-negative faces (happy and neutral) (Pegna et al, 2008, 2011; Del Zotto and Pegna, 2015; Vukusic et al, 2017). The P1 ERP component has a positive peak around 80–120 ms in the lateral occipital electrodes.…”
Section: Introductionmentioning
confidence: 99%